2010
DOI: 10.1159/000313361
|View full text |Cite
|
Sign up to set email alerts
|

Thrombotic Events in Patients with Congenital Prekallikrein Deficiency: A Critical Evaluation of All Reported Cases

Abstract: The occurrence of thrombotic events in patients with congenital bleeding conditions has received considerable attention in recent years. The same is true for asymptomatic defects of factors of the contact phase of blood coagulation, mainly FXII. Anecdotal reports on thrombosis in patients with prekallikrein deficiency have occasionally been reported. These involved both arterial and venous thrombosis. The purpose of the present article is to analyze the stories and the clinical pictures of all 75 cases of prek… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 73 publications
(48 reference statements)
1
26
1
Order By: Relevance
“…Twenty-one out of the 89 patients had hypertension or hypertension-related conditions [6,8,12,14,15,[17][18][19][20][21][22][23][24][25][26][27][28][29][30]. Twelve were men and nine women (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty-one out of the 89 patients had hypertension or hypertension-related conditions [6,8,12,14,15,[17][18][19][20][21][22][23][24][25][26][27][28][29][30]. Twelve were men and nine women (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Thrombotic events have been occasionally reported in patients with prekallikrein deficiency [17], but no study has ever been dedicated to the prevalence of hypertension and its complications in these patients.…”
Section: Introductionmentioning
confidence: 99%
“…There is scant data on a role for PKK in human thromboembolism. Only ϳ 75 cases for congenital PKK deficiency have been published, 7,8,29 precluding meaningful epidemiologic analysis, and an association between elevated PKK levels and thrombosis has not been established. 49 Small molecule inhibitors, antibodies and ASOs targeting fXI or fXIa are currently under development for therapeutic use.…”
Section: Discussionmentioning
confidence: 99%
“…Humans and other animals deficient in a contact activation protein are largely asymptomatic. 4,[6][7][8] However, the contact system may play an important role in thrombotic disease, as pharmacologic inhibition of fXIIa or ablation of the fXII or HK genes can protect mice from experimentally induced thrombosis in a variety of models. [9][10][11][12][13] Interestingly, fXII deficiency confers somewhat greater protection from thrombosis than fXI deficiency in some models, 11 implying that fXII may contribute to thrombus formation through additional pathways distinct from fXI-dependent intrinsic pathway activation.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the mechanistic relevance of PKK and f12 in HAE, our rationale for targeting these proteins via antisense drugs is enhanced by the limited pathophysiology associated with deficiencies of either of these proteins in humans. Humans with complete deficiencies of PKK are asymptomatic (Girolami et al, 2010a;Girolami et al, 2010b); f12 deficiency has been correlated with a predisposition towards increased venous thrombosis (Ratnoff, 1980), though the mechanism by which this occurs remains to be elucidated, as other prothombotic factors may be involved (Girolami et al, 2004). Moreover, case-controlled studies have not found an association between f12 deficiency and adverse outcomes (Koster et al, 1994;Zeerleder et al, 1999) and severe f12 deficiencies are not associated with increased mortality (Endler et al, 2007).…”
Section: Discussionmentioning
confidence: 99%